Differences in cold adaptation of Bacillus subtilis under anaerobic and aerobic conditions - Beranová, Jana; Mansilla, María C; de Mendoza, Diego; Elhottová, Dana; Konopásek, Ivo (Journal of bacteriology, 2010)
Bacillus subtilis, which grows under aerobic conditions, employs fatty acid desaturase (Des) to fluidize its membrane when subjected to temperature downshift. Des requires molecular oxygen for its activity, and its expression is regulated by DesK-DesR, a two-component system. Transcription of des is induced by the temperature downshift and is decreased when membrane fluidity is restored. B. subtilis is also capable of anaerobic growth by nitrate or nitrite respiration. We studied the mechanism of cold adaptation in B. subtilis under anaerobic conditions that were predicted to inhibit Des activity. We found that in anaerobiosis, in contrast to aerobic growth, the induction of des expression after temperature downshift (from 37 degrees C to 25 degrees C) was not downregulated. However, the transfer from anaerobic to aerobic conditions rapidly restored the downregulation. Under both aerobic and anaerobic conditions, the induction of des expression was substantially reduced by the addition of external fluidizing oleic acid and was fully dependent on the DesK-DesR two-component regulatory system. Fatty acid analysis proved that there was no desaturation after des induction under anaerobic conditions despite the presence of high levels of the des protein product, which was shown by immunoblot analysis. The cold adaptation of B. subtilis in anaerobiosis is therefore mediated exclusively by the increased anteiso/iso ratio of branched-chain fatty acids and not by the temporarily increased level of unsaturated fatty acids that is typical under aerobic conditions. The degrees of membrane fluidization, as measured by diphenylhexatriene fluorescence anisotropy, were found to be similar under both aerobic and anaerobic conditions.
Keywords: buněčná membrána; fluidita membrány; signální transdukce; Signal Transduction; anaerobióza; Anaerobiosis; Bacillus subtilis; Adaptation, Physiological; aerobióza; Aerobiosis; nízká teplota; bakteriální proteiny; Cold Temperature; regulace genové exprese u bakterií; desaturasy mastných kyselin; mastné kyseliny; Fatty Acid Desaturases; Membrane Fluidity; Gene Expression Regulation, Bacterial; Bacterial Proteins; fyziologická adaptace; Cell Membrane; Fatty Acids